Nudging toward vaccination: a systematic review - Reñosa, Mark Donald; Landicho, Jeniffer; Wachinger, Jonas; Dalglish, Sarah L.; Bärnighausen, Kate; Bärnighausen, Till; McMahon-Rössle, Shannon A. (BMJ global health, 2021)
Background Vaccine hesitancy (VH) and the global decline of vaccine coverage are a major global health threat, and novel approaches for increasing vaccine confidence and uptake are urgently needed. ‘Nudging’, defined as altering the environmental context in which a decision is made or a certain behaviour is enacted, has shown promising results in several health promotion strategies. We present a comprehensive synthesis of evidence regarding the value and impact of nudges to address VH. - Methods We conducted a systematic review to determine if nudging can mitigate VH and improve vaccine uptake. Our search strategy used Medical Subject Headings (MeSH) and non-MeSH terms to identify articles related to nudging and vaccination in nine research databases. 15 177 titles were extracted and assessed following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The final list of included articles was evaluated using the Mixed Methods Appraisal Tool and the Grading of Recommendations, Assessment, Development and Evaluations framework. - Findings Identified interventions are presented according to a framework for behaviour change, MINDSPACE. Articles (n=48) from 10 primarily high-income countries were included in the review. Nudging-based interventions identified include using reminders and recall, changing the way information is framed and delivered to an intended audience, changing the messenger delivering information, invoking social norms and emotional affect (eg, through storytelling, dramatic narratives and graphical presentations), and offering incentives or changing defaults. The most promising evidence exists for nudges that offer incentives to parents and healthcare workers, that make information more salient or that use trusted messengers to deliver information. The effectiveness of nudging interventions and the direction of the effect varies substantially by context. Evidence for some approaches is mixed, highlighting a need for further research, including how successful interventions can be adapted across settings. - Conclusion Nudging-based interventions show potential to increase vaccine confidence and uptake, but further evidence is needed for the development of clear recommendations. The ongoing COVID-19 pandemic increases the urgency of undertaking nudging-focused research. - PROSPERO registration number CRD42020185817.
Gesehen am 02.12.2021